Dilemma in two game structures for a closed-loop supply chain under the influence of government incentives - Subrata Saha; Izabela Ewa Nielsen; Sani Majumder (Journal of Industrial Engineering International, 2019)
The government organizations grant incentives to promote green product consumption, improve green product quality, boost remanufacturing activities, etc. through various policies. The objective of this study is to highlight pros and cons of two incentive policies, namely (1) incentive on manufacturer's R&D investment and (2) direct incentive to consumer based on greening level of the product on the optimal pricing and investment decisions in improving used product return and greening level decisions in a closed-loop supply chain (CLSC). Optimal decisions are derived under manufacturer and retailer-Stackelberg games, and results are compared to explore characteristics of optimal decisions, consumer surplus, and environmental improvement under two marketing strategies of a manufacturer. It is found that the greening level and used product return rate in a CLSC are always higher under retailer-Stackelberg game. If the manufacturer sets a target for greening level, the CLSC members may receive higher profits if consumer receives incentive because of higher consumer surplus. However, environmental improvement may be lower. If the manufacturer sets a product return goal, then CLSC members may compromise with consumer surplus or environmental improvement for receiving higher profits. In the presence of direct incentive to consumers, CLSC members can trade with product at lower greening level for higher profits. Moreover, investment in improving used product return is always less compared to the investment in improving greening level.
Keywords: 650; Closed-loop supply chain; Government incentives; Remanufacturing; Stackelberg game